The Brief Case: Acute Gangrenous Appendicitis with Incidental Schistosoma Eggs in a Malian Migrant - Harold Bermúdez-Marval; José Sanz-Moreno; Elena Aguirregoicoa Garcia; Ramón Pérez-Tanoira (The American Journal of Tropical Medicine and Hygiene, 2026)
ABSTRACT. Acute appendicitis is a common surgical emergency worldwide, but appendiceal involvement by Schistosoma species is rare, particularly in nonendemic settings.1 We report a 28-year-old male migrant from Mali presenting to the emergency department with 24 hours of right lower abdominal pain, anorexia, and low-grade fever. Physical examination and elevated inflammatory markers suggested acute appendicitis. Abdominal ultrasound demonstrated a thickened, noncompressible appendix with surrounding fat stranding. The patient underwent urgent laparoscopic appendectomy, which revealed a gangrenous, perforated appendix with localized inflammatory exudate. Histopathological evaluation unexpectedly identified numerous Schistosoma ova embedded throughout the appendiceal wall, surrounded by eosinophilic granulomatous inflammation, compatible with chronic schistosomal infection complicated by acute bacterial appendicitis. Postoperative recovery was uneventful; because of transfer of care, definitive antiparasitic therapy could not be administered locally. This case underscores the need to consider imported parasitic infections in the differential diagnosis of acute abdomen among migrants from endemic regions in nonendemic countries.1 It also highlights the crucial role of multidisciplinary collaboration among clinicians, surgeons, pathologists, and microbiologists for accurate diagnosis and appropriate management.